2021
DOI: 10.3389/fimmu.2021.707728
|View full text |Cite
|
Sign up to set email alerts
|

Viability Status-Dependent Effect of Bifidobacterium longum ssp. longum CCM 7952 on Prevention of Allergic Inflammation in Mouse Model

Abstract: The classical definition of probiotics states that bacteria must be alive to be beneficial for human organism. However, recent reports show that inactivated bacteria or their effector molecules can also possess such properties. In this study, we investigated the physical and immunomodulatory properties of four Bifidobacterium strains in the heat-treated (HT) and untreated (UN) forms. We showed that temperature treatment of bacteria changes their size and charge, which affects their interaction with epithelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 62 publications
1
12
0
1
Order By: Relevance
“…The mouse model of airway inflammation was performed as described previously [21]. Mice ( n = 4–10 per group) were divided into three experimental groups: SHAM, OVA, and EPS/OVA.…”
Section: Methodsmentioning
confidence: 99%
“…The mouse model of airway inflammation was performed as described previously [21]. Mice ( n = 4–10 per group) were divided into three experimental groups: SHAM, OVA, and EPS/OVA.…”
Section: Methodsmentioning
confidence: 99%
“…Besides correlation analysis showed that immune indicators are closely related to the production of SCFA ( 107 ). Oral administration of Lactobacillus rhamnosus diminished the characteristics of allergic asthma in a mouse model and induced immunomodulatory effects by a CD4 (+) CD25 (+) Foxp3 (+) Treg cell-mediated mechanism ( 108 ). Oral administration of Lactobacillus rhamnosus GG prevents OVA-induced allergic airway inflammation by amplifying mesenteric CD103+ DCs and accumulating mucosal Tregs cells.…”
Section: Allergic Asthmamentioning
confidence: 99%
“…Además, el análisis de correlación mostró que los indicadores inmunitarios se relacionan estrechamente con la producción de SCFA [107]. La administración oral de Lactobacillus rhamnosus redujo los signos del asma alérgica en un modelo murino e indujo efectos inmunomoduladores por un mecanismo mediado por células Treg CD4 + CD25 + Foxp3 + [108]. La administración oral de Lactobacillus rhamnosus GG previene la inflamación alérgica de las vías respiratorias inducida por OVA mediante la amplificación de las DCs CD103 + mesentéricas y la acumulación de células Treg mucosales.…”
Section: Asma Alérgicaunclassified